Controllability analysis and controller design for variable‐pitch propeller quadcopters with one propeller failure. Issue 2 (22nd February 2020) - Wang, Zhikun; Groß, Roderich; Zhao, Shiyu
Abstract : This article studies a relatively new type of aerial platform: variable‐pitch propeller (VPP) quadcopters. Unlike conventional fixed‐pitch propellers that can only generate upward thrust forces, a VPP can adjust its pitch angle to generate either upward or downward thrust forces. This provides VPP quadcopter with high agility and strong maneuverability. Although VPP quadcopters have attracted some attention recently, their potential has not been fully explored yet. In this article, we study the fault‐tolerant property of VPP quadcopters when one of the four VPPs fails to provide any forces or torques. We identify the equilibrium state in this case and conduct the controllability analysis based on a linearized model. This shows that the system remains controllable even if one propeller fails. As a result, simple linear‐quadratic regulator controllers can be used to control the platform. Although the controllability analysis and controller are based on the linearized model, numerical simulation incorporating measurement noises and external disturbances verifies the theoretic findings. Abstract : Graphical Abstract This article studies a relatively new type of aerial platform: variable‐pitch propeller (VPP) quadcopters. We identify the equilibrium state in this case and conduct the controllability analysis based on a linearized model. As a result, simple linear‐quadratic regulator controllers can be used to control the platform even if one propeller fails.